NATURE IN IRIS MURDOCH'S THE SEA, THE SEA - G. M. Adhyanggono (Soegijapranata Catholic University, 2010)
Iris Murdoch The Sea, The Sea is a novel which uses nature as its background or setting. This article particularly intends to give its attention to the aspects of nature delineated in the novel. In other words, this study is aimed at identifying, classifying, and describing aspects or elements of nature in it. It is also important to describe the relationship between these aspects and the story, as well as the characters. In addition, the tenets of